Cutaneous adverse reactions to acyclovir: case reports. - Robinson, G E (1985)
Intravenous, oral, and topical formulations of acyclovir have been successful in treating genital herpes. We report on two patients who developed skin reactions while taking acyclovir, which resolved when treatment was stopped.